Guanaco management by pastoralists in the Southern Andes - Lichtenstein, Gabriela (2012)
Background: As with most wild ungulates, guanacos (Lama guanicoe) overlap their range with domestic livestock resulting in a conflict for the use of rangelands between local livelihoods and conservation. This article explores a multiple-objective project that was set up in the La Payunia Provincial Reserve (Mendoza, Argentina) in order to address conservation of a migratory population of guanacos; desertification processes; and poverty alleviation. This study analyses the potential for guanaco use and management by a low-income Cooperative, the socio-economic impacts derived from the use, and the challenges facing the experience. Results: The Cooperative Payún Matrú was formed in 2005 mainly by local goat herders with a subsistence economy, thus providing a unique example where the beneficiaries of guanaco use are a low-income community. The project was successful in articulating the agendas of several stakeholders. A model for guanaco use under high animal welfare standards was developed as well as an alternative source of income for local people. Conclusions: The case study illustrates how a conflict over the use of grassland between domestic livestock and a wild species could be turned into an opportunity for economic diversification for pastoralists. Lessons are drawn that could contribute to policy decisions as well as sustainable use programmes for other wildlife species.